Daily Feeding of Fructooligosaccharide or Glucomannan Delays Onset of Senescence in SAMP8 Mice. (2nd June 2014) - Nakamura, Sadako; Kondo, Naoyuki; Yamaguchi, Yoshitake; Hashiguchi, Michiru; Tanabe, Kenichi; Ushiroda, Chihiro; Kawahashi-Tokuhisa, Miho; Yui, Katsuyuki; Miyakoda, Mana; Oku, Tsuneyuki
Abstract : We hypothesized that daily intake of nondigestible saccharides delays senescence onset through the improvement of intestinal microflora. Here, we raised senescence accelerated mice prone 8 (SAMP8) on the AIN93 diet (CONT), with sucrose being substituted for 5% of fructooligosaccharide (FOS) or 5% of glucomannan (GM), 15 mice per group. Ten SAMR1 were raised as reference of normal aging with control diet. Grading of senescence was conducted using the method developed by Hosokawa, and body weight, dietary intake, and drinking water intake were measured on alternate days. Following 38 weeks of these diets we evaluated learning and memory abilities using a passive avoidance apparatus and investigated effects on the intestinal microflora, measured oxidative stress markers, and inflammatory cytokines. Continuous intake of FOS and GM significantly enhanced learning and memory ability and decelerated senescence development when compared with the CONT group. Bifidobacterium levels were significantly increased in FOS and GM-fed mice. Urinary 8OHdG, 15-isoprostane, serum TNF- α, and IL-6 were also lower in FOS-fed mice, while IL-10 in FOS and GM groups was higher than in CONT group. These findings suggest that daily intake of nondigestible saccharides delays the onset of senescence via improvement of intestinal microflora.